Brill's Companion to Military Defeat in Ancient Mediterranean Society - Clark, Jessica Homan (Brill's Companions to Classical Studies: Warfare in the Ancient Mediterranean World Ser, 2017)
Intro -- Contents -- Preface -- List of Figures, Maps, and Tables -- Notes on Abbreviations -- Notes on Contributors -- Part 1 Introduction -- Chapter 1 Thinking about Military Defeat in Ancient Mediterranean Society -- Part 2 The Ancient Near East -- Chapter 2 Ideology, Politics, and the Assyrian Understanding of Defeat -- Chapter 3 The Assassination of Tissaphernes: Royal Responses to Military Defeat in the Achaemenid Empire -- Chapter 4 Achaemenid Soldiers, Alexander's Conquest, and the Experience of Defeat -- Part 3 Classical Greece and the Hellenistic World -- Chapter 5 Military Defeat in Fifth-Century Athens: Thucydides and His Audience -- Chapter 6 Demosthenes, Chaeronea, and the Rhetoric of Defeat -- Chapter 7 Spartan Responses to Defeat: From a Mythical Hysiae to a Very Real Sellasia -- Chapter 8 "No Strength To Stand": Defeat at Panium, the Macedonian Class, and Ptolemaic Decline -- Part 4 The Roman World -- Chapter 9 Defeat and the Roman Republic: Stories from Spain -- Chapter 10 The Ones Who Paid the Butcher's Bill: Soldiers and War Captives in Roman Comedy -- Chapter 11 Defeated by the Forest, the Pass, the Wind: Nature as an Enemy of Rome -- Chapter 12 Imperial Reactions to Military Failures in the Julio-Claudian Era -- Chapter 13 "By Any Other Name": Disgrace, Defeat, and the Loss of Legionary History -- Chapter 14 Recycling the Classical Past: Rhetorical Responses from the Roman Period to a Military Loss in Classical Greece -- Chapter 15 The Roman Emperor as Persian Prisoner of War: Remembering Shapur's Capture of Valerian -- Part 5 Epilogue -- Looking Ahead -- Index.